Photochemistry : new research - Smith, Abigail B.; Johnson, Nathan A., 1962- (Chemistry research and applications series., 2013)
The study of chemical reactions that proceed with the absorption of light by atoms or molecules is known as photochemistry. Everyday examples include photosynthesis, the degradation of plastics, and the formation of vitamin D with sunlight. In this book, the authors discuss new research in photochemistry, including the photoprotective role of mycrosporine-like aminoacids; bicarbonate-enhanced photocatalytic degradation of phenol; conformational relaxation of excitons in conjugated polymers; and the quenching of flavin triplets by amino acids and hydrophilic carotenoids.